Coalition formation - Wilke, Henk A.M (North-Holland, 1985)
A comprehensive view of coalition formation is presented here. Each of the chapters gives a summary of theories and research findings in a specific field of interest, at various levels of human and primate organisation.
Advances in psychology ; 24
Keywords: Psychology; psychologie; psychologie, klinická psychologie